2018
DOI: 10.1021/acs.jnatprod.7b00722
|View full text |Cite
|
Sign up to set email alerts
|

ent-Jungermannenone C Triggers Reactive Oxygen Species-Dependent Cell Differentiation in Leukemia Cells

Abstract: Acute myeloid leukemia (AML) is a hematologic malignancy that is characterized by clonal proliferation of myeloid blasts. Despite the progress that has been made in the treatment of various malignant hematopoietic diseases, the effective treatment of AML remains very challenging. Differentiation therapy has emerged as a promising approach for leukemia treatment, and new and effective chemical agents to trigger the differentiation of AML cells, especially drug-resistant cells, are urgently required. Herein, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As a readout, we performed a flow cytometry assay of the drugs using the myeloid surface marker CD11b, whose expression correlates with morphological and functional differentiation in NB4 cells 15,40,41 . According to literature 40,41,42,43,44,45,46 , many investigational drugs do not significantly induce differentiation in NB4 cells unless combined with ATRA. We thus hypothesised that PML-RARα could be a critical target, and a core component which inhibits differentiation-inducing pathways or mechanisms.…”
Section: Experimental Validation Of Cmap-predicted Drugsmentioning
confidence: 99%
“…As a readout, we performed a flow cytometry assay of the drugs using the myeloid surface marker CD11b, whose expression correlates with morphological and functional differentiation in NB4 cells 15,40,41 . According to literature 40,41,42,43,44,45,46 , many investigational drugs do not significantly induce differentiation in NB4 cells unless combined with ATRA. We thus hypothesised that PML-RARα could be a critical target, and a core component which inhibits differentiation-inducing pathways or mechanisms.…”
Section: Experimental Validation Of Cmap-predicted Drugsmentioning
confidence: 99%
“…Interestingly, in addition to HSP70, Fabrizio et al also identified peroxiredoxin‐1 (PRDX1) as a cellular target of oridonin 47 . PRDX1 is overexpressed in AML 115 and is a thiol reductase that plays a critical role in oxidative stress by neutralizing ROS 116 . Therefore, the increase in ROS by oridonin may be associated with its binding to GSH, TrxR, and Trx, as well as PRDX1.…”
Section: Direct Cellular Targets Of Oridonin and Its Derivative Compo...mentioning
confidence: 99%
“…Our group focuses on the use of bioactive small molecules to probe fundamental biological systems through a forward chemical genetic approach (Figure ). With the aim of discovering novel Nrf2 (nuclear factor erythroid 2-related factor 2) activators as lead compounds for the development of chemoprotective agents, ent -kaurane diterpenoid-pterisolic acid B was discovered from over 3000 compounds, and total synthesis is required as a kick-off course for understanding the MOA of ent -kauranes. Ultimately, we have demonstrated that pterisolic acid B shows a significant cytoprotective effect against cisplatin-induced cytotoxicity by covalently modifying cysteine-171 of keap1 (Kelch-like ECH-associated protein 1) .…”
Section: Total Syntheses Of Ent-kaurane Diterpenoids Through Radical ...mentioning
confidence: 99%